Peran Tindak Tutur Direktif dalam Novel Keluarga Cemara 2 Karya Arswendo Atmowiloto - Anastasya Fiandri Putri; Any Budiarti; Aries Setia Nugraha (FKIP, Universitas Palangka Raya, 2024)
Directive speech acts are one of the crucial aspects in the study of linguistic pragmatics that reflect how speakers use language to influence the actions or responses of their interlocutors. Utterances such as commands, requests, orders, and suggestions are concrete examples of this speech act. A profound understanding of directive speech acts helps us comprehend the complexity of human communication and social interactions in various contexts. Directive speech acts not only dominate everyday conversations but also constitute a significant element in literature, especially in novels. This research aims to analyze the directive speech acts contained in the novel